Influence of proinflammatory stimuli on the expression of vascular ribonuclease 1 in endothelial cells. Issue 2 (30th October 2013) - Gansler, Julia; Preissner, Klaus T.; Fischer, Silvia
Abstract : Extracellular RNA (eRNA) released under injury or pathological conditions has been identified as a yet unrecognized vascular alarm signal to induce procoagulant, permeability‐promoting, and proinflammatory activities. eRNA‐induced functions were largely prevented by administration of RNase1 as a natural blood vessel‐protective antagonist of eRNA. The aim of this study was to investigate the inflammatory regulation of endothelial cell RNase1, which is partly stored in Weibel‐Palade bodies of these cells. Long‐term treatment of human umbilical vein endothelial cells (HUVECs) with inflammatory agents like tumor necrosis factor α (TNF‐α) or interleukin 1β (IL‐1β), but not with eRNA, significantly decreased the release (34±5%; 34±7% of control) as well as the cellular expression (19.5±5%; 33±8% of control) of RNase1. Down‐regulation of RNase1 by TNF‐α stimulation or RNase1 siRNA knockdown increased the permeability of HUVEC monolayers, demonstrated by dearrangement of VE‐cadherins at cell‐cell borders. Mechanistically, cytokine‐induced decrease of RNase1 expression did not involve the nuclear factor κ B (NFκB) signaling pathway but epigenic modifications. Since inhibition of histone deacetylases resulted in recovery of RNase1 expression and secretion after cytokine treatment, an acetylation‐dependent process of RNase1 regulation is proposed. These results indicate that cytokine‐mediated down‐regulation of RNase1 in endothelial cells may aggravate eRNA‐induced inflammatory activities and thereby disturbs the vascular homeostasis of the extracellular RNA/RNase system.—Gansler, J., Preissner, K. T., Fischer, S. Influence of proinflammatory stimuli on the expression of vascular ribonuclease 1 in endothelial cells. FASEB J. 28, 752–760 (2014). www.fasebj.org